Ultra‐high‐b radial diffusion‐weighted imaging (UHb‐rDWI) of human cervical spinal cord. Issue 1 (29th April 2018) - Thapa, Bijaya; Sapkota, Nabraj; Lee, YouJung; Jeong, Kyle; Rose, John; Shah, Lubdha M.; Bisson, Erica; Jeong, Eun‐Kee
Abstract : Background: Injury in the cervical spinal cord (CSC) can lead to varying degrees of neurologic deficit and persistent disability. Diffusion tensor imaging (DTI) is a promising method to evaluate white matter integrity and pathology. However, the conventional DTI results are limited with respect to the specific details of neuropathology and microstructural architecture. In this study we used ultrahigh‐b radial‐DWI (UHb‐rDWI) with b‐values ranging from 0 to ∼7500 s/mm 2 and calculated decay constant (DH ) at the high b‐values, which gives much deeper insight about the microscopic environment of CSC white matter. Purpose: To evaluate a novel diffusion MRI, UHb‐rDWI technique for imaging of the CSC. Study Type: Longitudinal. Subjects: Four healthy controls, each scanned twice. Field Strength/Sequence: 3T/2D single shot diffusion‐weighted stimulated echo planar imaging with reduced field of view. Assessment: The signal from each pixel of b0 (b = 0) and b‐value (b ≠ 0) images were fitted to a biexponential function and normalized. The signal‐b curve is obtained by dividing the latter curve by the former. DH was obtained from the curve at b >4000 s/mm 2 . A Monte‐Carlo Simulation (MCS) was performed to investigate how DH changes upon the increased water‐exchange at the CSC. Results: The signal‐b curves plotted at multiple levels of healthy CSC are almost identical on two successive scans and show a biexponential decay behavior: fast exponential decay at lower b‐values and much slower decay at UHb‐values. The mean values of DH were measured as (0.0607 ± 0.02531) ×10 ‐3 and (0.0357 ± 0.02072) ×10 ‐3 s/mm 2 at the lateral funiculus and posterior column, respectively. MCS of diffusion MRI shows that the DH is elevated by increased water exchange between the intra‐ and extraaxonal spaces. Data Conclusion: UHb‐rDWI signal‐b plots of the normal CSC were highly reproducible on successive scans and their biexponential decay behavior can be used to characterize normal spinal white matter. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:204–211.